A Practice in using E-Portfolio in a Higher Education Course Taught at Distance - Karaoglan, B.; Ertaul, L. (Elektronika ir Elektrotechnika, 2010)
The aim of this study is to explore recent research and developments on using e-portfolios (EP) in innovative learning and instruction and to transfer an experience in using EP in a higher education course tought at distance. Computer Network Security course will be deliverd online over the Blackboard arhitecture. The course material consists of video lectures, transcripts of the videos, assignments and the syllabus. Interactions among the students and the lecturer are via email, discussion forums and EP comments. EPs will be evaluated from achievement assessment and learning support perspectives. Although creating and using EPs is a built in function in most of educational software, literature related to practices using e-portolios in e-learning in higher education is sparse.